(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, who made praise the key to His remembrance, a reason for more of His bounty, and a proof ofHis grace and majesty, which made the Qur’an the light of mankind, enlightening its path and making it happy.Now, the interpretive studies of the Holy Qur’an have multiplied with the multiplicity of approaches of the interpreters.Some of them interpreted the Qur’an linguistically, some interpreted it jurisprudentially, and some interpreted it rationally.Interpretations according to the knowledge and culture of the interpreter. The graphic approach in the interpretation of the Qur’an is one of these.Genres and falls under the linguistic and grammatical interpretation because its discussions revolve around the eloquence of the Qur’an inIts graphic image, such as similes, metaphors, euphemisms, representations, connections, separations, and what derives from that.Real or figurative use, euphemism, elicitation of image, structure evaluation, orInvestigating the verbal and intangible relationships or revealing the current and descriptive connotations, and researching thisThe aspect is an original research in the essence of the Quranic miracle and an accurate indicator of the knowledge of rhetoric.Quranic.